Learning Arabic Language by Analyzing the Linguistic Expressions in the Verses of Surah al-Fatikhah l Ta’allum al-Lugah al-‘Arabiyyah min Khilali Tahlil al-Ta’birat al-Lugawiyyah fi Ayati Surah al-Fatikhah - Setiyawan, Agung; Ainin, Moh.; Bahruddin, Uril; B. Sapar, Ahmad Arifin (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2021)
Surah Al-Fatikhah is very important to understand, because this surah is the main surah in the Qur’an which contains several hidden meanings that need to be understood by every Muslim. Surah Al-Fatikhah must be read in every prayer, but several people do not understand its meaning. This paper aimed to reveal the secrets of sentence phrases in the Surah Al-Fatikhah. The research data were obtained from several classical books (tafsir) and several journal articles discussing Surah Al-Fatikhah. The results showed that Surah Al-Fatikhah contains an implicit message which is reflected in 3 main points, namely: (1) the sentence, such as: deleting alif in the bismillah sentence, the use of "al" in the word ‘Hamdu’ and ‘Alamin’ (2) the word choice, such as: the use of the word al-Rahman, al-Rahim, Rabb al-'Alamin, Malik, Yaum al-din , al-Sirat, al-Mustaqim, al-Magdub, and al-Dallin and (3) sentence structure such as: a statement in the form of a sentence with the intention of the command used in the sentence ‘al-Hamdu lillahi Rabbil ‘Alamin, especially an objective in the expression of “Iyyaka Na'budu wa Iyyaka Nasta’in” as in the study of Balagah chapter al-Qasr in Ma'ani, and equating the word “al-Sirat al-Mustaqim” with al-Din al-Ḥaq as in the study of Balagah chapter al-Majaz in Bayan. Therefore, through this research, by understanding the meaning of the message contained in the Surah Al-Fatikhah, it would hopefully help a Muslim become more motivated in performing prayers.